Elevation of serum squamous cell carcinoma antigen 2 in patients with psoriasis: associations with disease severity and response to the treatment. (18th May 2016) - Watanabe, Y.; Yamaguchi, Y.; Komitsu, N.; Ohta, S.; Azuma, Y.; Izuhara, K.; Aihara, M.
Abstract : What's already known about this topic? Squamous cell carcinoma antigen (SCCA) belongs to the ovalbumin–serpin family. Serum SCCA level has been widely used as a tumour marker. Serum SCCA level is increased in patients with psoriasis. What does this study add? SCCA2 level was significantly higher in patients with psoriasis than healthy volunteers in both skin and serum. Serum SCCA2 level was strongly correlated with psoriasis severity score and reflected treatment efficacy. Expression of SCCA2 was elevated in the epidermis of patients with psoriasis and its intensity was correlated with serum SCCA2 level. SCCA2 was strongly induced by T‐helper (Th) 17‐type cytokines in human keratinocytes. What is the translational message? SCCA2 may be a useful biomarker in psoriasis, reflecting Th17‐type inflammation. Linked Comment: Yamanaka and Mizutani. Br J Dermatol 2016; 174: 1191–1192 . Plain language summary available online Summary: Background: Squamous cell carcinoma antigen (SCCA) belongs to the ovalbumin–serpin family and is a known tumour marker. Expression of SCCA is upregulated in the serum and skin of patients with psoriasis. Objectives: The aim of this study was to determine SCCA2 levels in association with disease severity and treatment efficacy in patients with psoriasis. Materials and methods: Patients with psoriasis ( n = 123) and healthy controls ( n = 25) were enrolled in this prospective cross‐sectional study. Enzyme‐linked immunosorbent assay (ELISA) analysis was performed to determine serum SCCA2 levels. SCCA2 expression in skin was evaluated using immunohistochemical analysis. Serum SCCA2 levels were compared with Psoriasis Area Severity Index (PASI) scores. The effect of treatment on serum SCCA2 levels was assessed using serial examinations. Induction of SCCA2 by several psoriatic cytokines in human keratinocytes was evaluated. Results: The serum levels of SCCA2 were significantly higher in patients with psoriasis than healthy controls and correlated well with disease severity. Increased SCCA2 staining was observed in lesional skin but not in nonlesional skin of patients with psoriasis. In addition, SCCA2 expression levels in skin correlated with serum concentrations of SCCA2. SCCA2 significantly decreased according to improvement of PASI scores. Interleukin (IL)‐17 and IL‐22 synergistically increased the production of SCCA2 at both mRNA and protein levels in human keratinocytes. Conclusions: Significant elevation of SCCA2 is associated with disease severity and reflects treatment efficacy. SCCA2 may be a useful biomarker in psoriasis, reflecting T‐helper 17‐type inflammation – the main determinant of the severity of psoriasis.